1992
DOI: 10.1161/01.cir.86.2.431
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the angiotensin converting enzyme inhibitor enalapril on the long-term progression of left ventricular dysfunction in patients with heart failure. SOLVD Investigators.

Abstract: In patients with heart failure and reduced LVEF, chronic ACE inhibition with enalapril prevents progressive LV dilatation and systolic dysfunction (increased ESV). These effects probably result from a combination of altered remodeling and sustained reduction in preload and afterload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
199
1
9

Year Published

1997
1997
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 502 publications
(223 citation statements)
references
References 35 publications
14
199
1
9
Order By: Relevance
“…19,20 Baseline dP/dt max values in the present study group were remarkably low despite the absence of bradycardia or systolic hypotension. Many previous studies of DCM in which patients with conduction delay were not targeted 8,[21][22][23] have reported consistent values for dP/dt max of Ϸ900 mm/s, 30% higher than in the present study but similar to values during pacing. Yet, the functional status, ejection fraction, etc, of the present patient group was indistinguishable from those in these previous studies.…”
Section: Discussionsupporting
confidence: 86%
“…19,20 Baseline dP/dt max values in the present study group were remarkably low despite the absence of bradycardia or systolic hypotension. Many previous studies of DCM in which patients with conduction delay were not targeted 8,[21][22][23] have reported consistent values for dP/dt max of Ϸ900 mm/s, 30% higher than in the present study but similar to values during pacing. Yet, the functional status, ejection fraction, etc, of the present patient group was indistinguishable from those in these previous studies.…”
Section: Discussionsupporting
confidence: 86%
“…Left ventricular remodelling is affected by various kinds of neurohumoral and local factors such as the renin–angiotensin–aldosterone system, the adrenergic nervous system, increased oxidative stress, proinflammatory cytokines, and endothelin 13, 14, 15, 16, 17. However, the precise mechanisms that cause LV remodelling are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9] Konstam et al reported that ACEI and -blockers can slow or reverse LV dilation and remodeling in patients with heart failure and the main effects of ACEI on LV dilation are observed in the first few months of therapy. 10 However, even after the introduction of these medications, there are still some cases that are difficult to manage medically and for these biventricular pacemaker therapy or surgical intervention, such as heart transplantation or the Batista procedure, are indicated. Therefore, risk prediction in patients with NIDCM is crucial for selection of the best treatment strategy.…”
Section: Discussionmentioning
confidence: 99%